INQUIRY LEARNING INNOVATION: EFFORTS TO DEVELOP INQUIRY-BASED TEACHING MATERIALS TO INCREASE MATHEMATICAL AND LANGUAGE LITERACY FOR MATHEMATICS STUDENTS AT UNIVERSITY - Alhusna, Asma; Gistituati, Nurhizrah; Ardi, Havid (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to develop and assess the effectiveness of inquiry-based teaching materials in enhancing both mathematical and language literacy among university-level mathematics students. Using the Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, the research involved second-semester students from the Mathematics program at Universitas Negeri Padang, selected through purposive sampling. Data were collected via questionnaires, observations, interviews, and tests assessing mathematical understanding and language literacy and analyzed through descriptive and inferential statistics along with thematic analysis for qualitative data. The results revealed significant improvements in student engagement, with 80% of participants reporting enhanced understanding and critical thinking. Furthermore, pre and post-test scores showed a notable increase in both mathematical and language literacy, from an average score of 60 in the pre-test to 78 in the post-test, alongside marked improvements in critical thinking, evaluation, and analysis skills. The findings demonstrate that the inquiry-based approach effectively promotes active learning and enhances both mathematical and language literacy. The novelty of this research lies in integrating inquiry-based learning to simultaneously address both cognitive and literacy skills in mathematics education, offering a more holistic approach to student development. This research suggests that incorporating such methods into the curriculum can foster more interactive, student-centered learning experiences, encouraging educators to adopt these approaches for improving critical thinking and literacy, thus enriching students’ academic and professional capabilities.